Additions to the genus Petalocephala Stål from India (Hemiptera: Cicadellidae: Ledrinae), with description of two new species - Rajgopal, Nernakallu N.; Gupta, Ankita; Ajaykumara, K. M. (Zootaxa, 2026)
Two new species of the tribe Ledrini, Petalocephala dweepa Rajgopal sp. nov. (Andaman Islands: Diglipur) and Petalocephala ishanya Rajgopal sp. nov. (Arunachal Pradesh: Hunli) are described and illustrated from India. The genus Petalocephala is reported from Andaman Is. (India) for the first time in this study. New locality record is also provided for Latycephala viridula Kuoh. All examined material is deposited in the National Insect Museum (NIM), ICAR—National Bureau of Agricultural Insect Resources, Bengaluru, India.